Alcohol and dietary factors associate with gut integrity and inflammation in HIV‐infected adults. Issue 6 (9th November 2016) - Webel, AR; Sattar, A; Funderburg, NT; Kinley, B; Longenecker, CT; Labbato, D; Alam, SM Khurshid; McComsey, GA
Abstract : Objectives: HIV‐infected adults have heightened monocyte activation and inflammation, at least partially as a consequence of altered gut integrity. The role of dietary factors in microbial translocation and inflammation and their downstream effect on markers of cardiovascular disease (CVD) have not been explored. Our purpose was to describe the longitudinal dietary patterns of HIV‐infected adults, and to examine the relationship between dietary intake, gut integrity, inflammation and subclinical markers of CVD in HIV‐infected adults. Methods: We conducted a secondary analysis of 147 HIV‐infected participants in a 96‐week randomized clinical trial of rosuvastatin as primary CVD prevention. Dietary intake was assessed using dietary recall; plasma gut integrity, monocyte activation and inflammation markers were measured using an enzyme‐linked immunosorbent assay (ELISA); and CVD risk was assessed using carotid ultrasound and the coronary artery calcium score. Linear mixed models were used to analyse longitudinally measured biomarkers. Results: The median age was 45 years and 78% of patients were male. At baseline, participants consumed a mean (standard deviation) of 108 (70) g of fat daily, 19 (15.6) g of fibre, 266 (186) g of carbohydrates and 15.6 (5.9) g of protein; 45% of the sample consumed alcohol. Over time, alcohol consumption was associated with several markers of gut integrity and inflammation (all P < 0.05). Conclusions: HIV‐infected adults in a contemporary, high‐resource setting have poor dietary patterns. Alcohol use was associated with worse gut integrity and increased inflammation, while other aspects of diet (fibre, carbohydrates and fat) were not. These data add to growing evidence illustrating the need for a better understanding of the effect of lifestyle factors on comorbidities in HIV‐infected adults.